EFECTO ANTIOXIDANTE Y ANTIFOTOENVEJECIMIENTO DE EXTRACTOS DE LA MACROALGA DEL LITORAL PERUANO DE Macrocystis integrifolia BORY Y ELABORACIÓN DE UNA FORMA DERMOCOSMÉTICA - Castro, Américo J. (2014)
The aim of the study was to evaluate the antioxidant and antiphotoaging effects of extracts of brown alga Macrocystis integrifolia Bory and develop a dermocosmetic form. From this extracts, was designed the dermocosmetic form in concentrations of 1, 3 and 5%, on a base made of lard with incorporation of beeswax and sesame oil to a pH of 6,5. The antioxidant activity was determined by in vitro methods as CDP and ABTS. The evaluation of antiphotoaging effect in vivo was performed using 25 albino female mice of Mus musculus specie, strain Bald / C53, who were divided into five groups of five mice each; except the group that served as blank, control and intervention groups were depilated hair back and subjected to UVB irradiation for 7 days, morning and night. The in vitro antioxidant activity assay showed that between extracts from stem, foliage and bulb of this alga, there are differences in antioxidant capacity against free radical ABTS, stating that the lower IC50 value (173,21 µg/mL) frond abstract presents higher total antioxidant capacity than the IC50 (3,23 µg/mL) value of Trolox, reference substance. In the trial CDP an IC50 value (669,7 µg/mL) was above the standard of ascorbic acid IC50 (33 µg/mL). Antiphotoaging analysis showed, at macro and microscopic levels, favorable notable differences in the intervention groups. Was conclude that brown seaweed extracts studied have antioxidant effect in vitro and antiphotoaging in vivo.